Virtual surgical planning and 3D printing: Methodology and applications in veterinary oromaxillofacial surgery - Klasen, Jan R. S.; Thatcher, Graham P.; Bleedorn, Jason A.; Soukup, Jason W. (Frontiers in Veterinary Science, 2022)
Virtual surgical planning is the process of planning and rehearsing a surgical procedure completely within the virtual environment on computer models. Virtual surgical planning and 3D printing is gaining popularity in veterinary oromaxillofacial surgery and are viable tools for the most basic to the most complex cases. These techniques can provide the surgeon with improved visualization and, thus, understanding of the patients’ 3D anatomy. Virtual surgical planning is feasible in a clinical setting and may decrease surgical time and increase surgical accuracy. For example, pre-operative implant contouring on a 3D-printed model can save time during surgery; 3D-printed patient-specific implants and surgical guides help maintain normocclusion after mandibular reconstruction; and the presence of a haptic model in the operating room can improve surgical precision and safety. However, significant time and financial resources may need to be allocated for planning and production of surgical guides and implants. The objectives of this manuscript are to provide a description of the methods involved in virtual surgical planning and 3D printing as they apply to veterinary oromaxillofacial surgery and to highlight these concepts with the strategic use of examples. In addition, the advantages and disadvantages of the methods as well as the required software and equipment will be discussed.